2008
DOI: 10.3748/wjg.14.2723
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between rpoB gene mutation in Mycobacterium avium subspecies paratuberculosis and clinical rifabutin and rifampicin resistance for treatment of Crohn’s disease

Abstract: The data clearly illustrates that clinical and in vitro-selected MAP mutants with rpoB mutations result in resistance to RIF and RFB, and that a single amino acid change in the beta subunit may have a significant impact on RIF resistance. Unconventional drug susceptibility testing such as our molecular approach will be beneficial for evaluation of antibiotic effectiveness. This molecular approach may also serve as a model for other drugs used for treatment of MAP infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…SNPs in a specific 81-bp region of the rpoB gene are associated with Rifampicin (RIF) resistance in M. tuberculosis [ 106 ]. Beckler et al [ 107 ] determined that several MAP isolates that were resistant to RIF and to Rifabutin, also had mutations in the rpo B gene (compared with K10). In the current study, the complete rpo B gene sequence was found to be identical in JIII-386, Telford and K-10.…”
Section: Resultsmentioning
confidence: 99%
“…SNPs in a specific 81-bp region of the rpoB gene are associated with Rifampicin (RIF) resistance in M. tuberculosis [ 106 ]. Beckler et al [ 107 ] determined that several MAP isolates that were resistant to RIF and to Rifabutin, also had mutations in the rpo B gene (compared with K10). In the current study, the complete rpo B gene sequence was found to be identical in JIII-386, Telford and K-10.…”
Section: Resultsmentioning
confidence: 99%
“…MAP, like other mycobacteria, has been shown to have the presence of resistant strains to Rifamycin compounds (including Rifampicin and Rifabutin), due to the presence of the rpoB gene. This will influence the response to AMAT [45][46][47].…”
Section: Patient Age Years Sex Prior Therapies Amat (Y/n) Amat Regimmentioning
confidence: 99%
“…Similar mutations in the rpoB genes of M. kansasii, M. leprae, the MAC, and M. ulcerans also confer rifamycin resistance (30,190,195,233,275), although a significant proportion of resistant MAC strains may lack a missense mutation in this gene (195). The most common mutations associated with clinically acquired resistance in M. tuberculosis cluster in an 80-bp region of the rpoB gene, with approximately 80% of isolates having a mutation in codon 526 or 531 (305,461).…”
Section: Inhibition Of Nucleic Acid Synthesismentioning
confidence: 99%